Behavior and design method for offset multi-wedges swaged couplers under uniaxial tension. Issue 4 (March 2021) - Liu, Zexin; Wang, Peijun; Liu, Yuanjian; Chen, Ying; Liu, Fangzhou
This paper proposed an Offset Multi-Wedges Swaged Couplers (OMWSC) as mechanical connection of steel rebars. The behavior of the connection consisting of two steel rebars connected by one OMWSC under uniaxial tension is investigated by Finite Element Model (FEM) simulations, which is verified through test results by considering the load-displacement curve, the failure mode and the failure deformation, and the insertion force to install the wedges. Parameter studies are carried out using the verified FEM. Studied parameters included the rebar surface type, the wedge diameter, the steel rebar diameter, the overlap ratio of the wedges that is defined as the ratio of wedge distance to the effective wedge distance, the extrusion ratio that is defined as a half of the wedge diameter to the gap of the two rebars, and the edge distance. Design equations for the coupler and the wedge of an OMWSC are proposed. Verification of the proposed design methods proved the OMWSC designed using the proposed method would not fail prior to the failure of steel bars.